Analysis of Digital Consumerism Based on Cultural, Economic, and Social Aspects in the Islamic Economic Framework - Herlina Yustati; Shahrul Nizam Bin Salahudin (Yayasan Darussalam Bengkulu, 2026)
Background: The advancement of digital technology has significantly changed people's consumption behavior, especially among Generation Z Muslims. However, studies that specifically measure digital consumerism within the framework of Islamic economics are still limited. This study aims to analyze digital consumerism based on cultural, economic, and social aspects, as well as develop a valid and reliable measurement instrument in accordance with Islamic values. Method: The method used is descriptive quantitative with a Likert scale questionnaire instrument consisting of 13 statement items. The instrument was tested on 30 Muslim generation Z respondents in Bengkulu Province through three validity and reliability tests using Minitab software. Results: The results showed that most statement items had correlation coefficients above 0.5 and a Cronbach's Alpha value above 0.94, signifying excellent internal consistency and reliability. The results of validity and reliability tests conducted three times using Minitab showed that out of 13 items, there were 8 items that were declared valid and reliable with a correlation value > 0.5 and Cronbach's Alpha above 0.94. Conclusion: This instrument is expected to be a reference for further research in measuring Islamic consumerism and as a basis for developing consumption education strategies that are in accordance with sharia principles in the digital era.